PENGARUH CUSTOMER RELATIONSHIP MANAGEMENT DAN EXPERIENTIAL MARKETING TERHADAP CUSTOMER SATISFACTION SERTA DAMPAKNYA PADA CUSTOMER LOYALTY (Suatu Studi pada PT Maddunia Wisata di Jakarta Selatan) - Rizal Zaen, Saeful (EKOBISMAN : JURNAL EKONOMI BISNIS MANAJEMEN, 2016)
The purpose of this research is to find the influence of customer relationship management and experiential marketing to customer satisfaction and its impact on customer loyalty PT Maddunia Wisata in Jakarta. Technique the sample collection the research uses judgment of sampling with the sample of the 225 consumers. Technique analysis the research uses sem-pls with software smartpls .The results of the study showed that customer relationship management significant to customer satisfaction to PT Maddunia Wisata, which means had been more effectively customer relationship management applied so will produce customer satisfaction higher. Variable experience marketing significant against customer satisfaction in PT Maddunia Wisata, which means been more effectively experience marketing applied will produce customer satisfaction higher.The findings showed that customer relationship management having influence positive and significantly to high low customer loyalty which means been more effectively customer relationship management applied will produce customer loyalty higher. Variable experience marketing having influence positive and significantly to high low customer loyalty in PT Maddunia Wisata, which means been more effectively experience marketing applied will produce customer loyalty higher. Based on the results of the analysis verifikatif, showed that customer satisfaction significant to customer loyalty This means the higher the level of satisfaction so will increase customer loyalty to PT Maddunia Wisata. Based on this fact, PT Maddunia Wisata can build strategy more effective relations, so that satisfaction will increase, which in turn would increase customer loyalty to companies and customer prospective other.